2019
DOI: 10.7717/peerj.7064
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and functional characterization of two dioxygenasese putatively involved in bixin biosynthesis in annatto (Bixa orellana L.)

Abstract: Carotenoid cleavage dioxygenases (CCDs) are enzymes that have been implicated in the biosynthesis of a wide diversity of secondary metabolites with important economic value, including bixin. Bixin is the second most used pigment in the world’s food industry worldwide, and its main source is the aril of achiote (Bixa orellana L.) seeds. A recent transcriptome analysis of B. orellana identified a new set of eight CCD members (BoCCD4s and BoCCD1s) potentially involved in bixin synthesis. We used several approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 55 publications
(83 reference statements)
2
26
0
Order By: Relevance
“…(Anguiano-Sevilla et al, 2018). The ESI conditions were a positive ion mode capillary voltage 32 Kv; SAMPLIng cone 42; source offset 80; and N2 cone gas flows: cone gas 50 1/h: desolvation gas 5000 MS/MS cone voltage: 35V and energy collision: 25V dry gas (Carballo-Uicab et al, 2019).…”
Section: Phenolic Compounds Identification By Uplc-esi/qtof/msmentioning
confidence: 99%
“…(Anguiano-Sevilla et al, 2018). The ESI conditions were a positive ion mode capillary voltage 32 Kv; SAMPLIng cone 42; source offset 80; and N2 cone gas flows: cone gas 50 1/h: desolvation gas 5000 MS/MS cone voltage: 35V and energy collision: 25V dry gas (Carballo-Uicab et al, 2019).…”
Section: Phenolic Compounds Identification By Uplc-esi/qtof/msmentioning
confidence: 99%
“…Furthermore, Ilg et al [208], using both in vitro and in vivo assays, demonstrated that the activity of OsCCD1 converts lycopene into pseudoionone (Figure 4) and MHO (Figure 5), suggesting that the 7,8(7 ,8 ) double bonds of acyclic carotenoid ends constitute a novel cleavage site for the CCD1 plant subfamily. Carballo-Conejo et al [222] also identified a CCD1 lycopene-specific 5,6(5 ,6 )-cleavage dioxygenase (BoCCD1-1) from Bixa orellana, responsible for the formation of bixin dialdehyde and MHO [223,224]. Bixin dialdehyde is the precursor for the formation of the dye bixin/annatto (Figure 5; see Section 3.6.1).…”
Section: Carotenoid Cleavage Dioxygenase 1 (Ccd1) Enzymes Cleave a Broad Category Of Carotenoids And Apocarotenoids At Multiple Double Bomentioning
confidence: 98%
“…BoCCD1-1 gene expression correlated with bixin accumulation in B. orellana [224], suggesting that BoCCD1-1 and its homologue BoCCD1-2 could be involved in the cleavage of lycopene in seed to form bixin. However, data from a study by Cárdenas-Conejo et al [222,223] indicated that although BoCCD1-1 is expressed in immature seed, it is also expressed in green tissue (leaf), and BoCCD1-2 was preferentially expressed in leaf. These authors also identified two additional CCD1 s, BoCCD1-3 and BoCCD1-4, which were shown to be expressed in immature seeds at 1.5-fold and 10-fold the levels found in leaf, respectively suggesting that BoCCD1-3 and BoCCD1-4 are more likely involved in the cleavage of lycopene to form bixin dialdehyde in the seed (Figure 5).…”
Section: Carotenoid Cleavage Dioxygenase 1 (Ccd1) Enzymes Cleave a Broad Category Of Carotenoids And Apocarotenoids At Multiple Double Bomentioning
confidence: 99%
“…Derived from achiote transcriptomes analysis, Cárdenas-Conejo et al (2015) identified eight candidate BoCCDs genes involved in bixin biosynthesis, distributed in hypothetical cytosolic and plastidic pathways, four of them belonging to the BoCCD1 subfamily: BoCCD1-1, BoCCD1-2, BoCCD1-3, and BoCCD1-4; and four of them to the BoCCD4 subfamily: BoCCD4-1, BoCCD4-2, BoCCD4-3 and, BoCCD4-4 (Cárdenas-Conejo et al, 2015). Recently, Carballo-Uicab et al (2019) demonstrated that the recombinant proteins BoCCD1-1 and BoCCD4-3 exhibited cleavage activity at the 5,6/5 ,6 positions of lycopene producing bixin aldehyde, indicating their involvement in the first step of bixin biosynthesis (Carballo-Uicab et al, 2019). Other BoCCD1 and BoCCD4 genes have been isolated from different B. orellana cultivars, but their role in bixin biosynthesis has not been unveiled (Rodríguez-Ávila et al, 2011b;Soares et al, 2011;Sankari et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Other BoCCD1 and BoCCD4 genes have been isolated from different B. orellana cultivars, but their role in bixin biosynthesis has not been unveiled (Rodríguez-Ávila et al, 2011b;Soares et al, 2011;Sankari et al, 2016). In general, the expression levels of all BoCCD genes identified in the transcriptomes increased in the immature stages of the seed (S3 and S4) when bixin reached its maximum levels and decreased in the mature stages of the seed (S5) when bixin levels dropped dramatically in the two accessions that produce contrasting levels of bixin (N4P and P13W) (Carballo-Uicab et al, 2019). Therefore, we hypothesize spatio-temporal participation in bixin biosynthesis of all the BoCCD1 and BoCCD4 enzymes identified in the transcriptomes of B. orellana.…”
Section: Introductionmentioning
confidence: 99%